Introduction to GNU Octave A brief tutorial for linear algebra and calculus students - Lachniet, Jason (Open textbook library., 2017)
This brief book provides a noncomprehensive introduction to GNU Octave, a free open source alternative to MatLab. The basic syntax and usage is explained through concrete examples from the mathematics courses a math, computer science, or engineering major encounters in the first two years of college: linear algebra, calculus, and differential equations.